PELATIHAN DESIGN THINKING SEBAGAI UPAYA MENINGKATKAN DAYA SAING IRT KERIPIK BAYAM BERKAH BAROKAH - Dian Ayu Liana Dewi; Muhammad Tahwin; Fajar sodiq; Rahma Auliya; Muhammad Ilham Al Asrori (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2025)
The purpose of this community service activity is to improve the competitiveness of the home industry (IRT) "Keripik Bayam Berkah Barokah". The activity was carried out through training based on the design thinking approach. The problems faced by the partner include simple product packaging, limited production equipment, and a lack of knowledge in business management. The training materials provided covered business motivation, creativity and innovation, as well as marketing strategies. The training was conducted using lectures, discussions, and practical sessions. The results of the training showed increased motivation, creativity, and innovation in product and packaging development, as well as the use of social media for promotion. In this program, the team also provided spinner and hand sealer equipment to support the improvement of product quality. Overall, the community service activity made a significant contribution to improving the partner's business management quality and competitiveness Keywords: Training, design thinking, competitiveness.